The Moderating Effect of Extraversion on the Big Five Personality Traits in the Relationship Between Pedagogical Competence and Kindergarten Teacher Performance - Titik Nurhidayatul Fitri; Yuli Kurniawati Sugiyo Pranoto; Edi Waluyo (Journal of Science and Education (JSE), 2024)
This study aims to determine the moderating effect of the Big Five personality domain of extraversion on the relationship between pedagogical competence and teacher performance. The research seeks to examine the contribution of the extraversion variable in the relationship between the independent and dependent variables. The subjects of this study are kindergarten teachers with two years of work experience in Semarang. This research is quantitative in nature, employing a correlational research design. Data collection was conducted through a Google Form questionnaire. The data analysis technique utilized descriptive analysis and fulfilled classical assumption tests, including Normality Test and Hypothesis Test. The results yielded a significance value of 0.000 and a beta value of 0.754 from the correlation test between pedagogical competence and teacher performance, indicating a strong relationship between these variables. After incorporating the moderator variable of extraversion into the correlation, the interaction coefficient obtained was (-0.039), leading to the conclusion that extraversion weakens the relationship between pedagogical competence and teacher performance. Based on these findings, it can be concluded that higher levels of extraversion among teachers may weaken their pedagogical competence, consequently affecting their performance.